2011
DOI: 10.1111/j.1750-3841.2011.02500.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Antioxidant Modification of Wheat Peptides Modified by the Heat and Lipid Peroxidation Product Malondialdehyde

Abstract: Wheat peptides, the biological active peptides derived from foods, has an array of biological actions, including antiobesity, antimicrobial, and angiotensin I-converting enzyme inhibitory effects in mammalian species. Recent studies showed that some wheat peptides may show the noteworthy antioxidant potency against the peroxidation of lipids or fatty acids, but the effect of oxidation on its antioxidant activities is unclear. In the present study, we demonstrate that heat and malandialdehyde (MDA)-oxidized whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…Modification of proteins by chemical derivatization in vitro has allowed studying MDA-mediated effects on a variety of carriers ranging from myelin proteins [53] to wheat peptides [54]. Reported observations of proteins modified in vivo with MDA were recently summarized by us elsewhere [16].…”
Section: Lipoprotein and Protein Carriersmentioning
confidence: 98%
“…Modification of proteins by chemical derivatization in vitro has allowed studying MDA-mediated effects on a variety of carriers ranging from myelin proteins [53] to wheat peptides [54]. Reported observations of proteins modified in vivo with MDA were recently summarized by us elsewhere [16].…”
Section: Lipoprotein and Protein Carriersmentioning
confidence: 98%
“…The FRAP assay is often used to evaluate the capacity of natural antioxidants to donate hydrogen or transfer electrons to transition metals responsible for catalysing the formation of harmful ROS/ free radicals. In fact, Tang et al (2012) have shown a direct correlation between enhanced antioxidant activities (measured as inhibition of ROS production) and the reducing power of natural peptides. In this assay, the ability of CPH and its RP-HPLC peptide fractions to reduce Fe 3+ to Fe 2+ was determined through changes in the absorbance at 700 nm of the supernatant of the reaction mixture; the higher the absorbance, the stronger the metal reducing power of the sample.…”
Section: Metal (Iron) Chelation and Reducing Propertiesmentioning
confidence: 98%
“…Even though the exact mechanisms underpinning the antioxidant effect are not well established, it is considered to be due to the metal ion chelating properties of His and scavenging properties [ 66 ]. While investigating the oxidative effect of wheat peptide antioxidant activity level, Tang et al [ 67 ] demonstrated that heat and malondialdehyde (MDA) oxidized wheat peptides and led to a loss of their antioxidant activity. Moreover, the authors noted that these oxidative conditions can induce peptide aggregation and a higher ROS production in vivo .…”
Section: Biological Activities and Underlying Cellular And Moleculmentioning
confidence: 99%